Statistical Approach for Water Glass Precursor Preparation from Bamboo Leaf Silica - Silviana Silviana; Bakti Jos; Herry Santosa; Siswo Sumardiono (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
The bamboo leaf consists of high silica content. In this study, the bamboo silica was utilized as water glass. Water glass can also be used as eco-friendly precursors for the preparation of silica aerogel. The extraction process of silica from bamboo leaf have been carried out through acid leaching and combustion process at 750°C based on thermal gravimetry analysis. This paper is aimed to assess the effect of two types of alkali hydroxide and concentrations producing water glass of bamboo leaf silica. The result was analyzed by using a 22-factorial design with six replications. The alkali hydroxide types were sodium hydroxide and potassium hydroxide with a concentration of 4 M and 6 M, respectively. The study was executed in several steps, i.e. pre-treatment of bamboo leaf, leaching process, combustion, purification of bamboo leaf silica and synthesis of water glass. The optimum condition of water glass products was obtained at silica concentration of 41.08 ppm and density of 1.23 g/L for potassium hydroxide, while at 40.15 ppm and 1.30 g/L for sodium hydroxide. ANOVA analysis resulted in a significant effect for type of hydroxide and concentration releasing model for silica concentration response. This study also characterized the silica structure and composition by instrumentation analysis for silica solid obtained from optimum water glass condition with potassium hydroxide. It can be denoted the physical behavior of silica solid from water glass by potassium hydroxide did not differ from previous research of water glass by sodium hydroxide.